Structural and magnetic properties of SiO2-CaO-Na2O-P2O5containing BaO-Fe2O3glass-ceramics - W. Leenakul (2018)
The incorporation method was employed to produce bioactive glass-ceramics from the BaFe 12 O 19 -SiO 2 -CaO-Na 2 O-P 2 O 5 glass system. The ferrimagnetic BaFe 12 O 19 was first prepared using a simple mixed oxide method, where the oxide precursors of 45S5 bioglass were initially mixed and then melted to form glass. The devitrification of Na 3 Ca 6 (PO 4 ) 5 and Fe 3 O 4 was observed in all of the quenched glass samples. The glass samples were then subjected to a heat treatment schedule for further crystallization. It was found that the small traces of BaFe 12 O 19 phases started to crystallize in high BF content samples of 20 and 40 wt%. These samples also exhibited good magnetic properties comparable to that of other magnetic glass-ceramics. The bioactivity of the BF glass-ceramics improved with increasing BF content as was evident by the formation of bone-like apatite layers on the surface of all of the glass-ceramics after soaking in SBF for 14 days. The results support the use of these bioactive glass-ceramics for hyperthermia treatment within the human body. © 2012 Elsevier B.V. All rights reserved.